2005
DOI: 10.1093/jncimonographs/lgi033
|View full text |Cite
|
Sign up to set email alerts
|

Building a Virtual Cancer Research Organization

Abstract: The CRN research management Web site and associated standardized data files and procedures represent a quasi-public resource, and the CRN stands ready to collaborate with researchers from outside institutions in developing and conducting innovative public domain research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
127
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(127 citation statements)
references
References 16 publications
0
127
0
Order By: Relevance
“…The details of the Network and the data sources used for this study have been described previously. 20,21 Funded by the National Cancer Institute under a cooperative agreement, the Network is a consortium of 14 research centers, which are affiliated with integrated health care systems that provide the continuum of cancer care for patients of all ages. The health care systems that participated in this study (Henry Ford Health System, Michigan; Group Health, Washington; and 4 Kaiser Permanente Regions-Colorado, Northwest [Oregon and southern Washington], and Northern and Southern California) are predominantly staff-model health care delivery systems.…”
Section: Settingmentioning
confidence: 99%
“…The details of the Network and the data sources used for this study have been described previously. 20,21 Funded by the National Cancer Institute under a cooperative agreement, the Network is a consortium of 14 research centers, which are affiliated with integrated health care systems that provide the continuum of cancer care for patients of all ages. The health care systems that participated in this study (Henry Ford Health System, Michigan; Group Health, Washington; and 4 Kaiser Permanente Regions-Colorado, Northwest [Oregon and southern Washington], and Northern and Southern California) are predominantly staff-model health care delivery systems.…”
Section: Settingmentioning
confidence: 99%
“…The following questions were addressed: All HMORN sites maintain a Virtual Data Warehouse (VDW) consisting of electronic medical record (EMR) and insurance claim data for their enrolled members. 24,25 Data on encounters, pharmacy fills, diagnoses, medical tests, and demographics are organized using the same definitions across sites and are quality checked locally. These data are matched to official regional mortality records using Social Security Numbers or patient names, birthdates, and demographic profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that expense patterns generated from SEER-Medicare and HMO data are roughly consistent (9)(10)(11); no studies, however, have systematically examined how cancer-specific and longitudinal patterns of resource and service use and overall expense differ between HMOs and Medicare. Building on the work of the Cancer Research Network [CRN (12)(13)(14)], the Burden of Cancer study (BURDEN) has developed a multisite, multipayer database to support analyses extending and complementing the linked SEER-Medicare data. Our study extends the literature on costs of cancer care to include nonaged adult HMO patients (aged 18-64 years) and adds HMO data to the literature that describes the cost experience for those aged 65 and over.…”
Section: Measuring the Medical Cost Of Cancermentioning
confidence: 99%
“…Data were standardized across health plans according to specifications established by the CRN's Virtual Data Warehouse (VDW) (12). In any analysis that compares utilization or cost data from multiple organizations or across delivery settings, it is critical that data be standardized to the largest extent possible.…”
Section: Data Sourcesmentioning
confidence: 99%